Misuse of topical corticosteroids over face: A clinical study - Kajal Manchanda; Sandip Mohanty; Pallavi C Rohatgi (Wolters Kluwer Medknow Publications, 2017)
Introduction: Topical corticosteroids (TCS) have been widely used in various dermatological diseases. However, because of inadvertent use, TCS misuse has become a common problem faced by dermatologists in various parts of the world. Prolonged use over the face can cause various side effects such as steroid rosacea, acneiform eruptions, and hypertrichosis. Aim: To study the effects of TCS misuse and analyze various factors promoting its use on face. Materials and Methods: A total of 100 patients presenting with various facial dermatoses following the misuse of TCS on the face were studied. Detailed history was noted and the various side effects were recorded. Results: Majority of the patients (70%) were females with maximum number of patients belonging to the age group of 11-20 years. Eighty-five percent of the patients were applying TCS for medical conditions, with acne being the most common indication, and the rest were applying as a general face cream. Pruritus and acneiform eruptions were the most common side effects observed and the other reported were erythema, photosensitivity, steroid dependent face, and telangiectasia. Conclusion: TCS misuse especially over the face can lead to a multitude of side effects. It is high time to create awareness among the patients as well as doctors regarding the proper usage of this wonder drug.